Teacher’s Perspective in Teaching Reading Comprehension Using Reciprocal Strategy - Leny Dwi Puspita; Ermawati Zulikhatin Nuroh (Universitas Pendidikan Mandalika, 2022)
The Indonesian government has determined that English is a compulsory subject in junior high schools, senior high schools, and universities. English in junior high school includes four mandatory skills: listening, reading, speaking, and writing. In the teaching process, teachers are expected to be perfect. The teacher must be